Unravelling acceptance in the light of technology: Insights, perspectives and a research approach - Schönian, Katja; Brechtelsbauer, Bastian; Hasreiter, Saskia (2023)
The notion of acceptance is a prominent framework for understanding the implementation and use of digital technologies. It has thus informed much of the existing scholarship in the fields of management and organisation, as well as information systems research. In what follows, members of the project "Transforming Digitally" reflect on the concept of technology acceptance from their different disciplinary perspectives.<br